Morphosyntactic characteristics of demonstratives in the kari’ña language - Beria, José; Bruzual, Silviapatricia (LETRAS, 2019)
Demonstratives are deictic terms whose basic function is to focus the listener’s attention on surrounding elements of the speaking situation. Basically, they are divided into pronominal and adnominal, although there are other typologies (see Diessel, 1999 and Dixon, 2003).The purpose of this study is to describe the morphosyntactic characteristics of demonstratives in the Kari’ña indigenous language. This work is of a descriptive nature from a functional typology perspective. Several descriptive- ethnographic fieldwork sessions were carried out in the indigenous communities of Cachama and Tascabaña in the state of Anzoátegui, Venezuela. An important lexical richness was found to formulate the concept of degree of proximity to the speaker: proximity, medial and distal. The demonstratives used for people and animals are different from those for objects. The system is distance-oriented since it is structured on the basis of a couple of semantic features related to distance.